Ocular injuries among patients with major trauma in England and Wales from 2004 to 2021 - Bashir, Mohammed Talha; Bouamra, Omar; Kirwan, James F.; Lecky, Fiona E.; Bourne, Rupert R. A. (Eye (London), 2024)
Background Ocular trauma is a significant cause of blindness and is often missed in polytrauma. No contemporary studies report eye injuries in the setting of severe trauma in the UK. We investigated ocular injury epidemiology and trends among patients suffering major trauma in England and Wales from 2004 to 2021. Methods We conducted a retrospective study utilising the Trauma Audit and Research Network (TARN) registry. Major trauma cases with concomitant eye injuries were included. Major trauma was defined as Injury Severity Score >15. Ocular injuries included globe, cranial nerve II, III, IV, and VI, and tear duct injuries. Orbital fractures and adnexal and lid injuries were not included. Demographics, injury profiles, and outcomes were extracted. We report descriptive statistics and 3-yearly trends. Results Of 287 267 major trauma cases, 2368 (0.82%) had ocular injuries: prevalence decreased from 1.87% to 0.66% over the 2004–2021 period ( P < 0.0001). Males comprised 72.2% of ocular injury cases, median age was 34.5 years. The proportion of ocular injuries from road traffic collisions fell from 43.1% to 25.3% while fall-related injuries increased and predominated (37.6% in 2019/21). Concomitant head injury occurred in 86.6%. The most common site of ocular injury was the conjunctiva (29.3%). Compared to previous TARN data (1989–2004), retinal injuries were threefold more prevalent (5.9% vs 18.5%), while corneal injuries were less (31.0% vs 6.6%). Conclusions Whilst identifying eye injuries in major trauma is challenging, it appears ocular injury epidemiology in this setting has shifted, though overall prevalence is low. These findings may inform prevention strategies, guideline development and resource allocation.